Role of tear vasoactive intestinal peptide on dry eyes after laser keratorefractive surgery - Yang Kang; Qi Hu; Xue Li; Zidan Guo; Qiong Wu; Hong Zhang (BMC Ophthalmology, 2023)
Abstract Background To explore the changes in vasoactive intestinal peptide (VIP) concentration in tears post laser-assisted sub-epithelial keratomileusis (LASEK) and femtosecond laser-assisted in situ keratomileusis (FS-LASIK) surgeries and related factors, possible association between postoperative dry eye symptoms and VIP concentration in tears, and factors influencing dry eye symptoms after different periods post LASEK and FS-LASIK surgeries. Methods In this prospective, non-randomized, longitudinal cohort study, 23 and 22 subjects were recruited and underwent LASEK and FS-LASIK, respectively. After conducting an intact ophthalmic examination and collecting relevant surgical data, all subjects were examined for VIP concentration in their tears using ELISAs, tear-film breakup time, ocular staining and ocular surface disease index questionnaire before surgery and 1 day, 1 week, and 1 month post-surgery. Results Tear VIP concentration increased significantly after both LASEK and FS-LASIK, with the highest concentration observed 1 week post-surgery (P ≤ 0.05). Tear VIP concentration correlated negatively with corneal ablation depth (AD). The extent of dry eyes was related to the operation method employed and postoperative recovery period. In FS-LASIK and LASEK subjects, dry eyes were mainly affected by the basic ocular surface status before surgery, and VIP concentration. Furthermore, in LASEK subjects, dry eyes were negatively correlated with AD. Conclusion VIP was stimulated and mobilized as an emergency protection post-refractive surgery and a trauma model affected by AD. It can indirectly indicate the inevitable relationship between postoperative dry eye and nerve injury. Elevated post-surgery tear VIP relieves dry eye symptoms, showing its neuroimmune role in regulating adverse injury stimulation. The present study provides a solution to the pathogenesis of postoperative dry eyes. Trial registration The trial registration number: 2021JS22. Date of registration: 10 May 2021.